Acute Loss of Cited2 Impairs Nanog Expression and Decreases Self-Renewal of Mouse Embryonic Stem Cells. (17th February 2015) - Kranc, Kamil R.; Oliveira, Daniel V.; Armesilla-Diaz, Alejandro; Pacheco-Leyva, Ivette; Catarina Matias, Ana; Luisa Escapa, Ana; Subramani, Chithra; Wheadon, Helen; Trindade, Marlene; Nichols, Jennifer; Kaji, Keisuke; Enver, Tariq; et al.
Abstract: Identifying novel players of the pluripotency gene regulatory network centered on Oct4, Sox2, and Nanog as well as delineating the interactions within the complex network is key to understanding self-renewal and early cell fate commitment of embryonic stem cells (ESC). While overexpression of the transcriptional regulator Cited2 sustains ESC pluripotency, its role in ESC functions remains unclear. Here, we show that Cited2 is important for proliferation, survival, and self-renewal of mouse ESC. We position Cited2 within the pluripotency gene regulatory network by defining Nanog, Tbx3, and Klf4 as its direct targets. We also demonstrate that the defects caused by Cited2 depletion are, at least in part, rescued by Nanog constitutive expression. Finally, we demonstrate that Cited2 is required for and enhances reprogramming of mouse embryonic fibroblasts to induced pluripotent stem cells. Stem Cells   2015;33:699–712